Unraveling geopolitical risk and economic dynamics: Implications for foreign portfolio investment inflow in Malaysia - Ng, Janice Yijan; Shum, Jun Wai; Ng, Lih Shing; Siah, Chun Fong (2024)
This study is conducted to unveil the impact of geopolitical risk and other economic factors such as economic growth, interest rate, and global risk on the capital inflow in Malaysia which is indicated by foreign portfolio investment. The data collected in this study is secondary data in quarterly form from quarter 1 of 2005 to quarter 4 of 2022, in total of 72 observations. The different sources such as Department of Statistics Malaysia, Bank Negara Malaysia, Yahoo Finance, World Bank and Matteo Iacoviello’s website are being explored to obtain the relevant data in this study. Moreover, EViews version 12 is being used as the analytic tool in this study, which is to conduct the unit root test, multiple linear regression, diagnosis checking, granger causality test and variance decomposition. In short, this study can conclude that there is a significant and negative relationship for the dependent variable, capital inflow in Malaysia, and the independent variables, interest rate, geopolitical risk and global risk while insignificant and positive relationship is obtained for the capital inflow in Malaysia and economic growth.